2020
DOI: 10.3389/fgene.2020.00877
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Transcriptome Analysis Reveals Potential Candidate Genes and Pathways Affecting Intramuscular Fat Content in Pigs

Abstract: Intramuscular fat (IMF) content plays an essential role in meat quality. For identifying potential candidate genes and pathways regulating IMF content, the IMF content and the longissimus dorsi transcriptomes of 28 purebred Duroc pigs were measured. As a result, the transcriptome analysis of four high-and four low-IMF individuals revealed a total of 309 differentially expressed genes (DEGs) using edgeR and DESeq2 (p < 0.05, |log 2 (fold change)| ≥ 1). Functional enrichment analysis of the DEGs revealed 19 hub … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…In the past, many studies have used low-density microsatellite markers to identify QTL associated with porcine IMF [ 5 , 6 , 7 ]. However, due to the low marker density, it is difficult to accurately locate the target genes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, many studies have used low-density microsatellite markers to identify QTL associated with porcine IMF [ 5 , 6 , 7 ]. However, due to the low marker density, it is difficult to accurately locate the target genes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin is involved in insulin sensitization, fat metabolism, immunity, and inflammation [37], and ADORA1 is responsible for anti-lipolysis [38]. Studies have reported that it is a candidate gene that affects the intramuscular fat content [39]. GNAS plays multiple important roles in cell fate determination and differentiation during osteogenic differentiation [40].…”
Section: Discussionmentioning
confidence: 99%
“…The novel-m0170-3p was a novel miRNA identified, and there was no study on novel-m0170-3p. ADIPOQ is related to lipid metabolism and adipocyte differentiation ( 54 , 55 ). ADIPOQ was potentially regulated by the XR_003585597.1-miR-376c-3p relationship pair in this study.…”
Section: Discussionmentioning
confidence: 99%